Criminal Liability for the Use of Electrified Cables: Legal Implications in Death Cases in Aceh - Rahmalisa, Rahmalisa; Wiratmadinata, Wiratmadinata; Nasution, Anhar (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2025)
The installation of electrical cables in community gardens is carried out to protect crops from wild animal disturbances. However, this practice sometimes results in casualties due to individuals unknowingly coming into contact with the electric cables in the vicinity of the gardens. This was the case in Bireuen and Aceh Timur, where fatalities occurred as a result of the installation of electrical cables in agricultural areas. This phenomenon becomes interesting to analyze from the perspective of criminal liability for the perpetrators. This study aims to analyze the criminal responsibility of individuals who install electrical cables that cause death and the resolution mechanisms employed in these cases. The research uses a normative legal research approach. The purpose of this method is to analyze legal norms and principles. The legal materials used in this study include primary legal materials such as the Indonesian Penal Code (KUHP), the Criminal Procedure Code (KUHAP), and Law No. 30 of 2009. The results of the study show that the installation of electrical cables leading to loss of life was caused by the perpetrator's negligence in adhering to safety standards. Although the initial intention of the installation was to protect the garden, this negligence resulted in the unforeseen consequence of causing someone's death. This act fulfills the elements of criminal negligence as regulated under Indonesian criminal law, thus the perpetrator can be held criminally responsible. The resolution pattern used in these cases follows the litigation route, using formal procedures as stipulated in the criminal justice system. [Pemasangan kabel listrik di kebun masyarakat dilakukan untuk melindungi hasil panen dari gangguan binatang buas. Praktik ini adakalanya memakan korban yang tidak mengetahui adanya pemasangan arus listrik di sekitar kebunnya. Seperti kasus yang terjadi di Bireun dan Aceh Timur di mana adanya kematian masyarakat akibat pemasangan kabel listrik di wilayah perkebunan. Fenomena tersebut menjadi menarik dianalisis dalam perspektif pertanggungjawaban pidana bagi pelakunya. Penelitian ini bertujuan untuk menganalisis pertanggungjawaban pidana terhadap pelaku pemasangan kabel listrik yang menyebabkan kematian dan penyelesaian yang ditempuh dalam menyelesaikannya. Penelitian menggunakan jenis penelitian yuridis normatif. Penggunaan metode ini bertujuan menganalisis norma dan kaidah hukum. Bahan hukum yang digunakan yaitu bahan hukum primer berupa KUHP, KUHAP dan UU Nomor 30 Tahun 2009. Hasil penelitian menunjukkan bahwa tindakan pemasangan kabel beraliran listrik yang berujung pada hilangnya nyawa disebabkan oleh kelalaian pelaku dalam mematuhi standar keselamatan. Meskipun tujuan awal pemasangan adalah untuk melindungi kebun, kelalaian tersebut menimbulkan dampak yang tidak terduga, yakni kematian orang lain. Perbuatan ini memenuhi unsur pidana kelalaian sebagaimana diatur dalam hukum pidana Indonesia, sehingga pelaku dapat dimintai pertanggungjawaban hukum. Pola penyelesaian yang digunakan yaitu melalui jalur litigasi yakni menggunakan jalur formal sebagaiaman yang berlaku dalam mekanisme sistem peradilan pidana].